Synthesis of TiO₂ different phase by DC magnetron sputtering - Dobrovolskiy, A.; Goncharov, A.; Kostin, E.; Frolova, E. (Вопросы атомной науки и техники, 2014)
The enhanced interest to synthesis of thin and extra-thin films using for surface materials modification continue to be quite actual up to now. A special attention is drawn to coatings having important for practical applications characteristics with costs-effective production. These may be the films of binary compounds of certain metals, particularly, titanium nitride and titanium oxide. The last compound possesses the utmost significance due to wide range of its unique physical, chemical and biological properties. Functional coatings of titanium dioxide synthesis with nanoscale thickness is of considerable interest since it allows essential economy of the material and the increase of manufacturing productivity with the decrease of production cost. To create a scientific basis of nanotechnologies researchers explore different coatings methods, including the ion-plasma methods. Among them, reactive magnetron sputtering seems to be promising: DC magnetron coating allows to deposit titania in amorphous and crystal phase and control results by variation of deposition conditions. The substrate material influences coating phase, as well as discharge characteristics. The thermal linear expansion coefficient does not influence line blue shift in Raman spectra of deposited films in our experiments. The influence of film annealing after deposition up to 800ºC on dioxide crystalline phase of the film is shown.